Stylistic Realization of Illocutionary Acts in Deadpool & Wolverine: A Pragma-Stylistics Analysis - Amelia Az-zahra Dalimunthe; Tesalonika L.A; Gifa Auzira Alivia; Rahmadsyah Rangkuti (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Language not only communicates information but also carries out social actions. Nevertheless, speech act theory has largely overlooked the role of stylistic decisions in influencing illocutionary purposes. The current research explores the stylistic expression of illocutionary acts in the action-comedy movie Deadpool & Wolverine (2024) focuses on sarcasm, hyperbole, and irony as essential linguistic tools. Utilizing Searle’s (1975) classification of illocutionary acts alongside Leech and Short’s (2007) pragma-stylistics framework, a total of 328 utterances were identified to include illocutionary acts, and 14 utterances were chosen deliberately for comprehensive pragma-stylistic examination. The analysis was conducted in three phases: illocutionary categorization, stylistic recognition, and pragma-stylistics analysis. The findings indicate that all five types of illocutionary acts, representatives, directives, commissives, expressives, and declaratives are expressed through stylistic devices that enhance, weaken, or reshape their communicative roles. Wolverine's dialogue is stylistically understated and straightforward in its propositions, while Deadpool's speech is stylistically intricate characterized by sarcasm, exaggeration, and irony. These findings indicate that stylistic form cannot be separated from illocutionary function. The study enhances pragma-stylistics by showing that action-comedy movies provide a vibrant setting for investigating how film dialogue generates meaning through the interaction of speech acts and stylistic structure.